PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN MODUL QT-BILINGUAL TERHADAP HASIL BELAJAR SISWA - Amalana, Husna; -, Sudarmin; -, Latifah (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2013)
Quantum teaching learning model supported by QT(Quantum Teaching)-bilingual moduleÂ emphasize optimization all multiple intelligences and learning style of students in learningÂ activities with TANDUR frame. This research aimed to find out the effect of quantum teachingÂ learning model supported by QT-bilingual module to the achievement of X grade students of SMAÂ in Kedungwuni, how much the effect magnitude, and how student response. This research usesÂ true experimental design with X.1 and X.8 classes as reasearch samples which determined byÂ cluster random sampling technique. Data were collected through documentation, test,Â observation and questionnaire method. The results of hypothesis test analysis showed correlationÂ and determination coefficient are 0.54 and 29.16%. The results of questionnaire stated that theÂ studentsâ response is very good to quantum teaching learning model assisted by QT-bilingualÂ module. Based on the analysis, it can be concluded that quantum teaching learning modelÂ assisted by QT-bilingual module effects on student learning outcomes by achieving the mediumÂ level of effect with contribution is 29.16%. Studentsâ response is very good actually to quantumÂ teaching learning model supported by QT-bilingual module.Keywords: Quantum Teaching, QT-Bilingual ModuleÂ